ACCOUNTABILITY AND TRANSPARENCY OF THE FINANCIAL REPORTS OF THE GAMPING GRAND MOSQUE - Alek Murtin; Erni Suryandari Fathmaningrum; Leni Cahaya Permata; Muhamad Rifandi (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2026)
Mosques are also places to carry out various righteous charitable activities, such as serving as venues for deliberation, weddings, and seeking solutions to problems occurring within the community, and so on. Mosques can be likened to spiritual pools that cleanse all forms of sin, impurity, and traces of negligence of a servant. The Gamping Grand Mosque is under the management of the Muhammadiyah Branch of Gamping. The management and the Mosque Prosperity Council of the Gamping Grand Mosque have the desire to have comprehensive financial reports covering all activities along with explanations of financial sources. Although they have had financial reports so far, these are limited to cash balance reports and are not yet based on financial accounting standards. The purpose of implementing ISAK No. 35 is so that the management of funds originating from the community can achieve transparency and accountability in the financial reporting of the Gamping Grand Mosque. Transparency means that financial management is carried out by being disclosed to stakeholders, while accountability refers to the responsibility of financial management to stakeholders by the mosque’s financial managers. At the Gamping Grand Mosque, this is pursued by conducting training on the preparation of financial reports based on ISAK No. 35, which is directly beneficial for its financial management. The aim is to provide understanding and techniques on how to prepare financial reports for the Gamping Grand Mosque that are easy to implement and comprehend, delivered through training followed by assistance in preparing mosque financial reports based on ISAK No. 35. Thus, participants from the Gamping Grand Mosque will be able to independently prepare financial reports in the form of a Balance Sheet and a Comprehensive Financial Statement